'I do not know what's that word in English, but I will tell you about my cousin': EFL learners' communication strategies in online oral discussion tasks. Issue 2 (4th March 2023) - Aljohani, Nouf J.; Hanna, Barbara E.
ABSTRACT: In a context in which opportunities for oral interaction are limited (English as a foreign language courses at a Saudi tertiary institution), we carried out an action research project evaluating the introduction of computer-mediated spoken language tasks with a group of intermediate learners. Although the students were confronted with multiple challenges ranging from unfamiliarity with educational technology, through recurrent bandwidth issues, to their own limited linguistic repertoires, they showed themselves able to participate in discussion with increasing facility and levels of responsibility for conversation management. In this paper, we focus on the communication strategies (CS) which they deployed to achieve this. While CSs were not the subject of explicit instruction, the students showed themselves able to draw on their repertoires and on the strategies implicitly modelled by their instructor over the six weeks of speaking activities using the SpeakApps platform. We examine what these strategies were: change in CSs over time; CS use in different conversational configurations (teacher-led group discussion; student-led group discussion and peer-peer pair discussion); impacts of the audio-only nature of discussion on CS choice. The paper points to promising directions for future practice and research.